"A STUDY ON AWARENESS OF AI TOOLS IN FINANCIAL EDUCATION WITH REFERENCE TO GEN Z" (CAHIERS MAGELLANES-NS, 2024)
As digital natives, Generation Z (Gen Z) stands at the forefront of a technological revolution that includes artificial intelligence (AI) tools poised to reshape financial education. From interactive financial chat-bots to personalized robot-advisors, AI offers immense potential to transform how young individuals approach financial literacy. This study investigates the level of awareness Gen Z has about AI tools in financial education, along with their perceived benefits and the challenges they face in adopting these innovations. Based on a sample of 123 university students and young professionals, the research reveals that, while Gen Z recognizes the value of AI in delivering tailored learning and real-time insights, they encounter obstacles such as limited accessibility, data privacy concerns, and inadequate hands-on experience. The study also highlights a significant age-related difference in AI tool adoption, where older Gen Z members exhibit greater engagement. These findings emphasize the urgent need for educational institutions to integrate AI tools into curricula, foster consistent use through interactive projects, and ensure equitable access to emerging technologies. By addressing these barriers, AI has the potential to elevate financial literacy, equipping Gen Z with the essential skills to navigate an increasingly digital and data-driven financial landscape.